Standardization of foreign language training in the context of integration into the European educational space (Pedagogy of Higher and Secondary Education, 2014)
Hamanyuk V. A., Amelina S. M. Standardization of foreign language training in the context of integration into the European educational space.The article deals with the question of implementation of European educational standards to the Ukrainian system of foreign language high education. The frame programs for English and German for professional communication (integration of multicultural components and autonomic learning aspects) are analyzed.
Keywords: frame program; multicultural competence; foreign language communicative competence; autonomic learning